Konsep sastera Islam mengikut Uthman El-Muhammady. (the concept of Islamic literature according to 'Uthman El-Muhammady) - Yaacob, Adli (2017)
This study is about the concept of Islamic Literature as proposed by Dr Uthman el- Muhammady who is known as a humble character and his piety. In spite of that he was undoubtedly an outstanding intellectual. He stressed on the spiritual aspect and saw its relation to realm of knowledge. In his proposed conceptualization of Islamic literature, he took on the subject in a different manner from other intellectuals. He always maintained therealtion between Islamic literature and tasawwuf although that he did not explicitly used the term Islamic literature initially. In his book (Understanding Islam, Man, Knowledge and Culture) he did dedicate a topic entitled (towards producing Islamic poetry tradition). After discussing the attribtues of Islamic literature from the standpoint of the relation between a literary figure and the Creator he concluded that Islamic Literature has the objectives to assert truthfulness that comes from a divine inspiration level, to preserve the existing values Islam, to convey sincerity, to assert the beauty of the Creator, having the symbols that emanate from purified mind and soul, its message is universal, positive, constructive spiritually thus having a very close tie with Tasawwuf. This concept, to certain extent gives us an enlightened understanding about the real origin of thought that is deeply rooted in the truth. If we really understand it, the difference with the secular orientation and other contemporary thoughts such as Islamic liberalism will become clear ; that these thought are in fact in contrast with with the Quran and Sunnah.